Exploring the Applicability of Meritocracy as a Framework for Analyzing Spatial Inequality - Lee, Shi-Chul (Journal of Korea Planning Association, 2025)
This paper proposes an analytical tool for investigating spatial inequality by examining the relationship between space and meritocracy. It describes the rhetoric, research, and reality of this concept, particularly in urban planning, and provides a conceptual framework. This study posits that analogous to individuals living in a modern meritocratic society, spatial units such as cities and neighborhoods address disparity, exclusion, and morality issues. Relevant social-science literature is reviewed, including education, economics, sociology, geography, and urban planning, to consider zoning, growth management, and gentrification. In South Korea, spatial meritocracy is particularly evident in the discrepancy between the capital region and the remainder of the county. Spatial inequality, where residents of certain neighborhoods enjoy exclusive benefits or have limited mobility within a city, is a pressing issue. By investigating the space-meritocracy relationship, this study seeks to establish a preliminary framework as well as identify the initial implications and future research directions. KCI Citation Count: 0